Analysis of Cash Waqf Management at The Wihdatul Ummah Batusangkar Islamic Education and Dakwah Foundation - Deni Putra, Muhammad; Yulia, Fitri (El-Qish: Journal of Islamic Economics, 2023)
The main problem in this study is the low knowledge of the people of West Sumatra about cash waqf, but the Wihdatul Ummah Batusangkar Foundation is still eager to collect cash waqf with the application of good management science in accordance with existing regulations. The purpose of this discussion is to find out the management of cash waqf management at the Wihdatul Ummah Batusangkar Islamic Education and Da'wah Foundation. The type of research the author uses is a type of field research (field research), with descriptive qualitative methods. The data collection technique that the author did was through interviews and through documentation. The data analysis technique is by systematically compiling data obtained from interviews, field notes, and documentation, by organizing data into categories, breaking down into units, synthesizing, compiling in patterns, choosing which ones are important and will be studied, and making conclusions. Findings. The results of this study indicate that the management of cash waqf management has not gone well, this is indicated by the amount of cash waqf collection which continues to decline every year, and the collection is still within the internal scope. In an effort to develop productive waqf, the Wihdatul Ummah Batusangkar Islamic Education and Da'wah Foundation has opened Qurrata A'yun mart and invested funds in new student admissions (PMB) in the procurement of clothing. While the inhibiting factor is that the socialization efforts carried out by the nazir regarding cash waqf to the community are not optimal, this is also due to the limited understanding of the community and inadequate human resources.